PELATIHAN KINERJA TENAGA PENJUALAN PADA UKM - Djakasaputra, Arifin; Mahanani, Zenita Dian; Rosyada, Maulin Amrina (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Sales force plays a crucial role in determining the success of a company's product sales. Therefore, it is important to understand the factors that determine sales force performance. The partner involved in this activity is a creative handicraft product business located in Serang, Banten. Based on the initial observation conducted online through a zoom meeting, the partner has not fully understood the factors that contribute to improving sales force performance. The method offered in this activity is training and socialization on the basic understanding of performance and the success factors that influence it. The results of the activity show that the training material was delivered smoothly, and the partner showed enthusiasm in receiving the information, as evident from active discussions between the partner and the PKM team. Additionally, the activity succeeded in enhancing the partner's knowledge to improve their sales force performance.